How Do Audit Committee Characteristics Affect the Quality of Financial Information? Evidence From Saudi Arabia and United Arab Emirates Companies - Sayaf Mohammed Algrady; Rongbing Huang; Ebrahim Mohammed Al-Matari (SAGE Open)
This study examines how audit committee size (ACZE), independence (ACIND), and meetings (ACMEET) affect earnings management (EM) in public non-financial companies in both Saudi Arabia (SA) and the United Arab Emirates (UAE). Based on 1,128 observations from 188 SA- and UAE-listed companies between 2016 and 2021, the comprehensive regression analysis shows that more extensive and independent mitigates earnings management. However, audit committee size (ACZE), and ACMEET meetings had little effect. The results also reveal that AC best mitigates EM in companies with minimal agency costs. Interestingly, ACIND restrained EM in companies with few political connections. However, prominent committees work best in firms with strong political connections. ACZE and independence protect companies immune to financial restatements against EM. Additionally, larger and more independent AC are inversely associated with EM in firms with low board compensation, highlighting their critical role in maintaining financial integrity. Firms with high board compensation have a weaker relationship. This study adds to the regional corporate governance literature on RCG. Analyzing AC characteristics helps clarify the relationship between AC and QFI and how they affect CG practices in different organizational areas in this region. Analyzing the characteristics of AC enables a more nuanced understanding of the relationship between AC and financial reporting quality, which adds depth to the understanding of how these characteristics operate in different organizational areas.